A relação entre a qualidade vocal metálica e as estruturas craniofaciais - Fadel, Congeta Bruniere Xavier (2014)
This study investigates the relations between the craniofacial structures and metallic voice quality. The purpose is to identify craniofacial characteristics in amateur singers with metallic voice quality through the assessment of orofacial myology (OM) and vocal acoustic analysis. This is a cross-sectional analytical study of quantitative character, with participation of 60 amateur singers, 30 of which with metallic vocal pattern, integrating the Experimental Group, and 30 individuals without this vocal quality, corresponding to the Control Group. The volunteers were submitted to a vocal acoustic evaluation, in which the values of the fundamental frequency and the formant frequencies F1, F2, F3 and F4 were measured, and an Orofacial Myology Evaluation, in which the following structures were examined: face, occlusion, jaw, lips, tongue and palate. Statistical analyzes indicate no significant differences between the two groups regarding the Fundamental Frequency, but Formants F2, F3 and F4 had significantly higher (sharper) values in metallic voices in usual tone. In the OM Evaluation, analyzes point to significant differences between the two groups, allowing the characterization of the Experimental Group as: Short Face (66.7 %), Facial Standard II (56.7 %), Angle occlusion Class II (56.7 %), Overbite (73.3 %) and Overjet (63.3 %), indicating the existence of common craniofacial characteristics between metal singers with vocal quality.